IMPLEMENTASI BLENDED LEARNING TERHADAP KEMAMPUAN PENALARAN DAN PEMECAHAN MASALAH MAHASISWA - Muthia Dewi; Sri Rezeki Maulina Azmi; Dailami Dailami (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2022)
Abstract: The purpose of this study was to find out how the application of the blended learning learning process in students' reasoning and problem solving abilities. This type of research is Classroom Action Research. Where the operations in this study are translated into 4 stages in the form of a cycle, namely the planning, action, observation and reflection stages. The subjects in this study were students of STMIK Royal Kisaran and the object in this study was the students' reasoning and problem solving abilities using the blended learning method. The research instruments in collecting data were initial tests, learning outcomes tests, interviews and observations. Based on the results of the study, it was obtained that the total score obtained from the implementation of learning in cycle 1 in the class was categorized as less successful with an average score of 2.25. The total score obtained in cycle 2 was categorized as less successful with an average score of 2.75. The total score obtained from the implementation of learning in cycle 3 is categorized as successful with an average score of 3.5. Thus, in cycle 3 the implementation of learning is categorized as successful. Keywords: Blended Learning; Reasoning Ability; Solving Abilit  Problem Abstrak: Tujuan penelitian ini adalah untuk mengetahui bagaimana penerapan proses pembelajaran blended learning dalam kemampuan penalaran dan pemecahan masalah mahasiswa. Jenis penelitian ini adalah Penelitian Tindakan Kelas. Dimana operasional dalam penelitian ini dijabarkan menjadi empat tahap yang berupa siklus yaitu tahap perencanaan, tindakan, observasi dan refleksi. Subjek dalam penelitian ini adalah mahasiswa STMIK Royal Kisaran dan objek dalam penelitian ini kemampuan penalaran dan pemecahan masalah mahasiswa menggunakan metode blended learning. Instrumen penelitian dalam mengumpulkan data adalah tes awal, tes hasil belajar, wawancara dan observasi. Berdasarkan hasil penelitian diperoleh Jumlah skor yang diperoleh dari pelaksanaan Pembelajaran pada siklus 1 di kelas dikategorikan kurang berhasil dengan rata-rata skor 2,25. Jumlah skor yang diperoleh pada siklus 2 dikategorikan kurang berhasil dengan rata-rata skor 2,75. Jumlah skor yang diperoleh dari pelaksanaan Pembelajaran pada siklus 3 dikategorikan  berhasil dengan rata-rata skor 3,5. Dengan demikian pada siklus 3 pelaksanaan pembelajaran dikategorikan berhasil.Kata kunci: Blended Learning; kemampuan penalaran; kemampuan pemecahan masalah